ANALISIS PENGARUH PENGALAMAN KERJA DAN PELATIHAN TERHADAP MUTU PELAYANAN DAN KINERJA TENAGA KESEHATAN RUMAH SAKIT ISLAM (RSI) SURABAYA - Dhinta Feritsya Chita; Wasis Budiarto; C. Sri Hartati (AKUNTANSI 45, 2022)
The results of the research show that: 1) Work experience has a negative and insignificant effect on the performance of health workers, indicated by the coefficient value of -0.030; 2) Work experience has a positive and significant effect on service quality, indicated by the coefficient value of 0.454; 3) Service quality has a positive and significant effect on the performance of health workers, as indicated by the coefficient value of 0.478; 4) Work experience has a negative and insignificant effect on the performance of health workers mediated by service quality, with a coefficient value of -0.017.